2015
DOI: 10.1186/s12967-015-0716-5
|View full text |Cite
|
Sign up to set email alerts
|

Open-label, multicenter, single-arm phase II DeCOG-study of ipilimumab in pretreated patients with different subtypes of metastatic melanoma

Abstract: BackgroundIpilimumab is an approved immunotherapy that has shown an overall survival benefit in patients with cutaneous metastatic melanoma in two phase III trials. As results of registrational trials might not answer all questions regarding safety and efficacy of ipilimumab in patients with advanced melanoma seen in daily clinical practice, the Dermatologic Cooperative Oncology Group conducted a phase II study to assess the efficacy and safety of ipilimumab in patients with different subtypes of metastatic me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(43 citation statements)
references
References 39 publications
1
40
0
2
Order By: Relevance
“…investigated the efficacy in everyday clinical practice. In this study, patients with previously treated mucosal melanoma showed a one‐year survival rate of roughly 14 %, while the percentage in those with previously treated unknown primary was 27 % . In another study by Zimmer et al., one‐year survival in patients with choroidal melanoma was 22 %, with a two‐year survival of 7 % .…”
Section: Clinical Efficacy Of Checkpoint Inhibitorssupporting
confidence: 44%
“…investigated the efficacy in everyday clinical practice. In this study, patients with previously treated mucosal melanoma showed a one‐year survival rate of roughly 14 %, while the percentage in those with previously treated unknown primary was 27 % . In another study by Zimmer et al., one‐year survival in patients with choroidal melanoma was 22 %, with a two‐year survival of 7 % .…”
Section: Clinical Efficacy Of Checkpoint Inhibitorssupporting
confidence: 44%
“…In an accompanying systematic review, the authors only identified three other papers reporting on patients with MUP who received immunotherapy (a phase II study, a retrospective cohort study, and one case report) and seven papers concerning targeted therapy (six case reports and one small prospective observational study reporting on one patient). The phase II single‐arm study reported a median OS duration of 9.9 months for patients with MUP who received ipilimumab . Other studies have reported on the survival in patients with stage III and IV MUP, but they have not specifically addressed treatment with novel agents …”
Section: Discussionmentioning
confidence: 99%
“…Recently, targeted therapy has brought about encouraging results in the treatment of cutaneous melanoma; however, its implementation in OMM is lagging, owing in part to the lack of reliable genetic alterations reported in these tumors. Furthermore, some studies suggest that patients with mucosal melanomas do not benefit from the use of checkpoint inhibitors, as do patients with cutaneous melanoma . Thus, given the lack of treatment options for these rare tumors, improving the understanding of OMM tumorigenesis may prove useful for rational drug design.…”
Section: Introductionmentioning
confidence: 99%